Analisis Penggunaan dan Dampak Layanan Utang Online Ilegal oleh Masyarakat di Surakarta - Amalia Nurhaliza; Abdul Rahman; Danang Purwanto (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
Globalization has provided an impact on the development of increasingly advanced technology, one of which is in the field of finance with the emergence of financial technology. There are four types of technology financial services, one of which is currently developing in Indonesia is online debt services.  This study discusses the use and impact of illegal online debt services by the public. This research uses descriptive qualitative research methods with a case study approach. The data were collected by conducting interviews with six selected informants using side purposive techniques. The results showed that the reason for using online debt services to pay for children's schooling, business capital, meet daily living needs, and pay previous debts. The driving factors are easy terms, fast processes, no collateral, and difficulty obtaining debt in other formal financial institutions. The impact is mainly intimidative collection and misuse of personal data to collect debts accompanied by threats that interfere with the economic, social and psychological comfort of illegal online debt borrowers.